Proposing a new anti-Covid-19 agent by using molecular docking and dynamics simulations - Izabella Rodrigues Fonseca da Silva; Luís Felipe Guerreiro Martins; Julliane Yoneda (Brazilian Journal of Pharmaceutical Sciences)
Abstract The Covid-19 pandemic, caused by SARS-CoV-2, was responsible for millions of deaths worldwide. The main protease (Mpro) of SARS-CoV-2 is considered one of the important drug targets for the treatment of Covid-19. Recent studies have shown that anisotine should be a potent Mpro inhibitor. In the present work, four oxoquinoline derivatives are proposed as candidates for Mpro inhibitors. The main functional group of these derivatives shows similarity to anisotine, and they are active against the HSV-1, as well as the latter. Molecular docking studies evaluated whether these compounds could be active against Mpro of SARS-CoV-2. Structural modifications were proposed on the oxoquinoline derivative which formed a more stable complex with Mpro and this proposal formed an even more stable complex besides exhibiting improvements in the toxicological profile. Molecular dynamics simulations indicated that derivatives proposed promote greater stabilization by complexing with Mpro than anisotine.